Immune and Nervous Systems Interaction in Endocrine Disruptors Toxicity: The Case of Atrazine - Galbiati, Valentina; Buoso, Erica; d'Emmanuele di Villa Bianca, Roberta; Paola, Rosanna Di; Morroni, Fabiana; Nocentini, Giuseppe; Racchi, Marco; Viviani, Barbara; Corsini, Emanuela (Frontiers in Toxicology, 2021)
Endocrine disruptors (ED) are natural and anthropogenic chemicals that can interfere with the hormonal systems at different levels. As such, ED-induced alterations in hormone functions have been implicated in many diseases and pathological conditions, including adverse developmental, reproductive, neurological, cardiovascular, and immunological effects in mammals. The fact that ED may compete with several endogenous hormones for multiple receptors and pathways is not always fully considered. This results in a complex response that depends on the cellular context in terms of receptors and interacting proteins and, thus, may differ between tissues and circumstances. Microglia, neurons and other immune cells are potential targets and still underappreciated actors in endocrine disruption. This review focus on the immune-neuro-endocrine network in ED toxicity and research gaps, using atrazine, as an example to highlight the complex interrelationship between immune, endocrine and nervous systems, and ED.